Unveiling the neutrophil-Notch2-ISC axis: asiatic acid’s therapeutic strategy in infectious colitis - Zou, Wenshu; Zhong, Minyong; Pei, Zerong; Chen, Yuxin; Deng, Wenwen; Li, Hui (Frontiers in Immunology, 2025)
IntroductionSalmonella-induced colitis is a global health burden characterized by intestinal barrier disruption and deficient epithelial repair that involves a critical interplay between neutrophil dynamics and intestinal stem cell (ISC) regeneration. Current therapies do not target this interplay and do not adequately address therapeutic need. This study investigated the therapeutic mechanism of asiatic acid (AA) in a murine Salmonella typhimurium (S.T) infection model, focusing on its effects on the neutrophil-Notch-ISC axis.MethodsBalb/c mice were administered S.T for 3 days to model S.T infection AA (10 mg/kg) was gavage administered to mice 6 h after the S.T infection. Neutrophil-deficient mice were generated by daily intraperitoneal injection of Ly6G for 3 days.ResultsMouse colons were analyzed histologically, and transcriptomic, network pharmacology, western blotting, and immunohistochemistry investigations were performed. AA restored mucosal integrity by upregulating tight junction proteins (occludin and claudin 1) and acidic mucin granules levels, and by rescuing ISC proliferation through suppression of Notch2/Hes5/Hey1 signaling. Multiomics analyses further revealed the modulation of neutrophil chemotaxis and inflammatory pathways by AA. Strikingly, neutrophil ablation reduced the efficacy of AA, confirming that AA acts via neutrophil-mediated containment of bacterial invasion and epithelial shedding.DiscussionBy revealing the neutrophil-Notch2-ISC axis as a pivotal regulator of mucosal repair, our findings show AA to be a dual-action therapeutic agent that synergizes immune containment and regenerative pathways. These findings highlight an aspect of S.T pathogenesis and underscore the potential of natural compounds to harmonize host defense and tissue regeneration, offering a transformative strategy for infectious colitis beyond conventional anti-inflammatory approaches